An outline history of China / edited by Bai Shouyi ; written by Yang Zhao [and six others] - Bai, Shouyi (China studies, 2008)
This book provides a brief introduction to the long historical development of China from ancient times to the founding of the People's Republic of China in 1949. It also gives an outline of contemporary Chinese geography, population, ethnicity and history, and proceeds to describe ancient human activity, and the social and historical meanings of ancient mythologies and legends. A concise account of the rise and fall of the Xia, Shang, Zhou, Qin, Han, Wei, Jin, Sui, Tang, Song, Yuan, Ming and Qing dynasties is also given. Subjects include politics, economy, military affairs, culture, laws, inventions, cultural relics, etiquette and customs, as well as class relationships, relationships among ethnic groups of China, and the relationship between China and foreign countries. An enlightening description of modern social reforms completes the book.